Drawing the new adventure cartoons : cool spies, evil guys and action heroes - Hart, Christopher, 1957- (Chris Hart Books/Sixth&spring Books, 2008)
"Learn to draw the funny characters you see in comics, on TV, in movies and in video games: spies, secret agents, saboteurs, sci-fi heroes, hilarious muscle guys and those evil, rotten and just plain bad guys you love to hate! Chris Hart shows you how to use body language, costumes, action lines and the secrets of cartoon composition to create memorable characters and exciting scenes."--P. [4] of cover.